2021
DOI: 10.1111/pcmr.12972
|View full text |Cite
|
Sign up to set email alerts
|

The role of melanocytes in the human choroidal microenvironment and inflammation: Insights from the transcriptome

Abstract: The choroid within the human eye contains a rich milieu of cells including melanocytes.Human choroidal melanocytes (HCMs) absorb light, regulate free radical production, and were recently shown to modulate inflammation. This study aimed to identify key genes and pathways involved in the inflammatory response of HCMs through the use of RNA-seq. Primary HCMs were cultured from donor choroids, RNA was extracted from control and lipopolysaccharide (LPS)-treated HCMs, and mRNA was sequenced.Functional annotation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Recent studies indicate that ITGA1 is associated with melanoma proliferation via the regulation of miR-3065-5p ( 25 ). In addition, as a mediator of cell-cell and cell-matrix adhesion, ITGA1 was differentially expressed in melanoma samples ( 26 ). In the present study, we found that ITGA1 expression levels in SKCM tissues are correlated with different stages of SKCM and with migration in SKCM.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate that ITGA1 is associated with melanoma proliferation via the regulation of miR-3065-5p ( 25 ). In addition, as a mediator of cell-cell and cell-matrix adhesion, ITGA1 was differentially expressed in melanoma samples ( 26 ). In the present study, we found that ITGA1 expression levels in SKCM tissues are correlated with different stages of SKCM and with migration in SKCM.…”
Section: Discussionmentioning
confidence: 99%
“…Choroidal melanocytes represent neural crest‐derived melanin‐producing cells, which are located abundantly in the human choroid (Nickla & Wallman, 2010). The functional roles of NCM include light absorption by cytoplasmic melanins, antioxidant protection and were recently shown to modulate inflammatory pathways (Cioanca et al, 2021; Wakamatsu et al, 2008). The UM is originated from melanocytes of the uveal tract, furthermore, more than 90% of cases involving the choroid (Park et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, human choroidal melanocytes were shown to respond to inflammation by increased expression of inflammatory cytokines and genes associated with cell adhesion and angiogenesis [26]. Impaired melanogenesis may impact ability of the choroid to respond to inflammation, leading to increased inflammation and a thicker choroid.…”
Section: Discussionmentioning
confidence: 99%